VIOLENCIA DEL GÉNERO Y CONSECUENCIAS PSICOLÓGICAS EN MUJERES EN EL CENTRO COMUNAL “CRISTO DEL CONSUELO” DE LA CIUDAD DE BABAHOYO. - NUÑEZ RUIZ LESLY DANIELA (2024)
The objective of this work is to demonstrate gender violence and the psychological consequences in women associated with the SAMUVI program “Care and Support Service for Women Victims of Violence” of the “Cristo Del Consuelo” Community Center, in the city of Babahoyo. Gender-based violence against women refers to any act of gender-based violence that results, or may result, in physical, sexual, economic or psychological harm or suffering to women, including threats of such acts, coercion or arbitrary deprivation. of freedom. Its effects can be devastating, affecting women's physical, mental and emotional health, as well as their ability to fully participate in society. The research was carried out with a population of 100 women, using a sample of 51 of them. A type of descriptive research was used with a mixed approach and a non-experimental design methodology. The data was collected through a structured survey to demonstrate whether the women had been victims of gender violence. Interviews were conducted to explore the psychological state of the participants and analyze the impact of gender violence. In addition, psychometric tests such as the Beck Depression Scale, the Hamilton Anxiety Scale (HAM-A) and the Rosenberg Self-Esteem Questionnaire (RSES) were used. Through these techniques and instruments, the stated objectives were achieved. The results obtained allowed us to identify a high percentage of women affected by some type of gender violence and the negative repercussions on their mental health.